2015
DOI: 10.5664/jcsm.5016
|View full text |Cite
|
Sign up to set email alerts
|

Bispectral Index in Evaluating Effects of Sedation Depth on Drug-Induced Sleep Endoscopy

Abstract: achieve a target effect site (brain) concentration of propofol. However, patients may lose consciousness at variable effect site concentrations (Ce), with a higher Ce being associated with higher upper airway critical closing pressure.6,7 Most DISE procedures are started shortly after the patients lose consciousness. Objective:To evaluate the effect of sedation depth on druginduced sleep endoscopy (DISE). Methods: Ninety patients with obstructive sleep apnea (OSA) and 18 snorers underwent polysomnography and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 37 publications
0
51
3
2
Order By: Relevance
“…BIS monitoring, used by anesthetists to maintain loss of consciousness (LOC) and prevent intraoperative awareness, is used during DISE to ensure adequate sedation levels in an attempt to simulate natural sleep. Regarding the drug doses, studies have already shown the impact between superficial and deep sedation of the same drug on the BIS index and DISE findings . BIS is considered a reliable method for monitoring and accurately predicting the sedative depth when propofol and midazolam are used but not when other anesthetics such as nitrous oxide and ketamine are used .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BIS monitoring, used by anesthetists to maintain loss of consciousness (LOC) and prevent intraoperative awareness, is used during DISE to ensure adequate sedation levels in an attempt to simulate natural sleep. Regarding the drug doses, studies have already shown the impact between superficial and deep sedation of the same drug on the BIS index and DISE findings . BIS is considered a reliable method for monitoring and accurately predicting the sedative depth when propofol and midazolam are used but not when other anesthetics such as nitrous oxide and ketamine are used .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the drug doses, studies have already shown the impact between superficial and deep sedation of the same drug on the BIS index and DISE findings. 42,43 BIS is considered a reliable method for monitoring and accurately predicting the sedative depth when propofol and midazolam are used but not when other anesthetics such as nitrous oxide and ketamine are used. [44][45][46][47] Dexmedetomidine, which acts on the alpha 2-adrenoceptors in the locus coeruleus, 24 produces physiological sleeplike phenomena by EEG and a characteristic arousable sedation, which is markedly different from that of other sedatives such as the GABA agonists propofol and midazolam.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have shown that the collapsibility of the UA increases with the depth of the sedation, according to Heiser et al, decision making does not change significantly if the sedation is lower than 60. Although lower levels of BIS have been related to N3 sleep phase, they could cause deep oxygen desaturation, significantly unsafe for the patient . BIS values may not be the same if dexmedetomidine is the drug of choice; moreover, there is variability among the patients in the level of sedation with the same BIS score.…”
Section: Observation Windowmentioning
confidence: 99%
“…Obstrüktif uyku apnesi (OSA) üst hava yolunun birçok seviyesinde obstrüksiyon ile karakterizedir (1). Bu obstrüksiyonun doğru bir şekilde değerlendirilmesi için çeşitli fizik muayene ve radyolojik tetkikler yapılmaktadır.…”
Section: Gı̇rı̇şunclassified